2000
DOI: 10.1007/s002849910053
|View full text |Cite
|
Sign up to set email alerts
|

Uniparental Mitochondrial Transmission in Sexual Crosses in Cryptococcus neoformans

Abstract: Restriction fragment length polymorphism (RFLP) in the large ribosomal RNA region of the mitochondrial DNA (mtDNA) was developed as a genetic marker for investigating mitochondrial transmission in sexual crosses of the human pathogenic basidiomycetous yeast Cryptococcus neoformans. Strain JEC20 of C. neoformans var. neoformans (mat a) was mated with six strains of C. neoformans var. grubii (mat alpha). Successful mating was indicated by the formation of hyphae and basidiospores. These basidiospores were examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
68
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 18 publications
7
68
0
Order By: Relevance
“…The second is that these introns appeared in these locations after separation of these species. Analysis of the mt large rRNA gene and NADH dehydrogenase subunit 2 of C. neoformans revealed that serotype AD strains had either the serotype A or serotype D mtDNA genotype (29). In the present study, we obtained almost similar results for the distribution of cyt b gene types in serotype AD strains.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The second is that these introns appeared in these locations after separation of these species. Analysis of the mt large rRNA gene and NADH dehydrogenase subunit 2 of C. neoformans revealed that serotype AD strains had either the serotype A or serotype D mtDNA genotype (29). In the present study, we obtained almost similar results for the distribution of cyt b gene types in serotype AD strains.…”
Section: Discussionsupporting
confidence: 80%
“…Restriction fragment length polymorphism (RFLP) analysis of mtDNA has been shown to be useful for estimating the relations between fungi (8, 10, 24). Xu et al (29) showed that the origin of mitochondria in C. neoformans is uniparental. RFLP analysis of the mt large rRNA gene and NADH dehydrogenase subunit 2 gene allowed efficient screening of the mtDNA of C. neoformans (28).…”
mentioning
confidence: 99%
“…Unilateral production of conjugation tubes by MATa, unidirectional transfer of nuclei from MATa to MATa (McClelland et al, 2004), uniparental (MATa specific) inheritance of mitochondria (Xu et al, 2000), presence of mating type-specific pheromone response MAP kinase cascade genes, and the phenotypic differences revealed between tup1 strains of the two mating types point to the dioecism in C. neoformans. Dioecism by definition denotes the separation of sexes: presence of male and female sex organs in two different individuals and sexual reproduction requiring nuclear transfer from male to female (Alexopoulos et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Dikaryotic hyphae are subsequently produced normally by the MATa cells and meiotic products (basidiospores) are borne on the resulting basidia (KwonChung, 1980;McClelland et al ., 2004) which mimics the situation in dioecious plants and animals. In support of this concept, mitochondrial inheritance in C. neoformans has been shown to be uniparental: meiotic products carry only MATa type mitochondria (Xu et al ., 2000).…”
Section: Introductionmentioning
confidence: 96%
“…First, strains of serotype A isolated from either nature or patients can mate with serotype D strains (e.g. Xu et al, 2000a). Second, clinical isolates of serotype AD typically exhibit heterozygosity at several enzymic loci, sharing alleles from both serotypes A and D strains (Brandt et al, 1993(Brandt et al, , 1995.…”
Section: Introductionmentioning
confidence: 99%